In vitro synergistic effect of biosurfactant produced by Bacillus subtilis MTCC 441 against drug resistant Staphylococcus aureus - Mohammad Irfanâ€ , Sushil Kumar Shahiâ€¡, P.K. Sharma (Journal of Applied Pharmaceutical Science, 2015)
Microorganisms are capable to produce a wide range of surface active metabolites which are known as biosurfactant. In the present study, the production of biosurfactant from Bacillus subtilis MTCC 441 and evaluation of its synergistic activities with known antibiotics against drug resistance Staphylococcus aureus were performed. Drops collapse grid method was developed for detection of biosurfactant production in the medium. The production of biosurfactant was done in previously defined Carvalho’s medium. The extraction of biosurfactant was done in chloroform: methanol (2:1 v/v) solvent. The synergistic activity of crude biosurfactant was determined by disc diffusion and minimum inhibitory concentration assay. The Staphylococcus aureus was found resistant against ampicillin-sublactum (10µg), ampicillin (25µg), and cloxacillin (5µg), which showed no zone of inhibition but in the combination of crude biosurfactant, the zone of inhibition were measured as 14 mm, 14 mm and 19 mm, respectively. The crude biosurfactant showed good synergy with most of the antibiotics used in the study. The results demonstrated that biosurfactant possesses considerable potentiality to break the resistance of the pathogen tested. In future, it can be used for the development of effective drug against resistant bacteria.
Keywords: Biosurfactant, drug resistant, synergistic effect, Bacillus subtilis, Staphylococcus aureus.